Sistema de gestión de la información académica en la Unidad Educativa Barreiro. - Alvario Garces, Peter Enrique (2023)
The recent degree project specifies an academic information management system for the educational institution "Unidad Educativa Barreiro de la provincia de Los Ríos". It was designed to automate the academic processes in the face of the imminent digital gap in which the pedagogical establishments incur and for which we suggest that the learning processes should be more evolutionary and technological, for the knowledge of new sources of information. In this way it is necessary to generate an internal, direct, effective communication through the parts that make up the educational institution, all the manual would be simplified in a matter of time and the development of the students would be in accordance with the learning that is being done in their day to day. The system has functionalities for students, administrative staff and teachers.